Removal of incense smoke and corollary particulate matter using a portable bipolar air ionizer in an unventilated setup - Gupta, Nishant; Agarwal, Ashok Kumar; Singhal, Rajeev Kumar; Jindal, Sanjay Kumar; Ali, Daoud; Wanale, Shivraj Gangadhar; Kumar, Goklesh; Yadav, Virendra Kumar; Patel, Ashish (Frontiers in Environmental Science, 2023)
Indoor air pollution-associated health risk is substantially higher than outdoor. Bipolar air ionizers are one of the most escalated indoor air cleaners, employed to enhance indoor air quality in recent years. Albeit, despite growing positive results, bipolar air ionizationassociated safety concerns such as byproduct ozone and efficacy against many indoor air pollutants have been questionable. Evidence of bipolar air ionizers' effect on incense smoke is also limited. The present study aims to assess a needlepoint technology-based bipolar air ionizer removal efficacy against incense smoke. To observe the average effect, a series of experiments was conducted in 0.16 m 3 size transparent glass boxes. Further removal efficacy of bipolar air ionizer (BAI eff.) was estimated by empirical equations from the particulate matter [PM2.5] (BAI eff. pm 2.5 ) and PM10 removal (BAI eff.pm10). Particulate matter was used as the marker of incense smoke in this study, The concentration of particulate matter, potential byproduct ozone, relative humidity, and temperature were monitored by a customized sensors-based air quality monitor. Bipolar air ionizer-associated average reduction of PM2.5 and PM10 concentration was observed by 74-75%. The overall efficacy of tested BAI (BAI eff) against incense smoke particulate proportion was 90 ±10 % in 0.16 m 3 boxes, compared to the control. Smoke removal efficacy tested bipolar air ionizer is vigorous in test boxes, and byproduct ozone was not exceeded abnormally. However, the marginal elevation in temperature and humidity (up to 5 °C or 21%) and humidity (1.8%) were observed in the test 3 box when the bipolar air ionizer was conducted. Results suggest that bipolar air ionizer could be an effective option for indoor incense smoke reduction.